THE ROLE OF THE SHARIA SUPERVISORY BOARD IN THE FRAMEWORK ENFORCING SHARIA PRINCIPLES AT THE INSTITUTE OF ISLAMIC BANKING IN SEMARANG - Aryani Witasari (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Indonesia as the country with the largest Muslim population in the world, since approximately 25 years ago trying to get out of the slump economic problems. One effort in doing it is to fix the economic system we particularly of financial institutions with a switch using Sharia system. Banking financial institution as the economic backbone of Indonesia sought to apply Islamic principles in accordance with the provisions of the Qur'an and Al Hadith and what is regulated in the Law Compilation of Islamic Economics. The application of Sharia principles in this new start in 1992, namely by in the operation of Bank Muamalat Indonesia. Prior to 1992, the Indonesian economy are not familiar with Islamic principles in accordance with the Qur 'syariah principle has been applied by the banking institutions including Bank Muamalat Indonesia is in a start since its establishment, the principle is divided into three areas : 1. Sharing System (avoid riba) 2. Buying and selling on margin system Advantages 3. system Services In general principles that must be enforced by Islamic banks is to avoid the usury and uses a system of revenue sharing as well as buying and selling. In order upholding Islamic principles that must be run by Islamic banks need supervision that have until now run by the Sharia Supervisory Board (DPS). DPS task as the supervisory board on Islamic banking is the attribution of authority. DPS is authorized by the original authority derived directly from Article 27 PBI No. 6/24 / PBI / 2004, which outlines the duties, powers and responsibilities of DPS, DPS Presence is what differentiates it from conventional banks. DPS is independent and equal position with BOC. Keywords: Role Sharia Supervisory Board Sharia Principles